Preparation and application of hydrophobic propane oxidative dehydrogenation catalyst

By introducing hydrophobic functional groups on the surface of the propane oxidation dehydrogenation catalyst, the hydrophobic catalyst is prepared, which solves the problem of the reduction of the activity of traditional catalysts under water molecules adsorption, significantly improves the water resistance and stability of the catalyst and extends the service life.

CN119386925APending Publication Date: 2025-02-07Institute of Intelligent Creation, Henan Academy of Sciences +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411492186.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

During the reaction, traditional propane oxidation dehydrogenation catalysts have reduced catalytic activity due to adsorption of water molecules, and water vapor in the metal catalyst system may cause metal phase separation, affecting catalytic performance.

Method used

The hydrophobic propane oxidation dehydrogenation catalyst is prepared by introducing hydrophobic functional groups on the surface of the catalyst to improve the water resistance and stability of the catalyst. The specific method includes supporting active components such as Pt and Sn on a SiO2 support and enhancing the hydrophobic properties of the catalyst by grafting different organic hydrophobic segments.

Benefits of technology

The activity and stability of the catalyst are significantly improved, the reaction or adsorption between water molecules and the catalyst surface is inhibited, and the metal phase separation is prevented, thereby extending the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386925A_ABST
    Figure CN119386925A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a hydrophobic propane oxidative dehydrogenation catalyst, and aims to inhibit reaction or adsorption of water molecules generated in the reaction process of the catalyst and the surface of the catalyst by introducing hydrophobic groups to the surface of the catalyst, so that the activity and stability of the catalyst are improved. According to the method, Pt and Sn active components are loaded on a SiO2 carrier, and then an organic hydrophobic chain segment is grafted to prepare the hydrophobic catalyst. The prepared catalyst shows excellent hydrophobicity, the water resistance is remarkably improved in the propane oxidative dehydrogenation reaction, the metal phase separation phenomenon is effectively inhibited, and the service life of the catalyst is prolonged. Related tests show that the catalyst is high in stability, less in carbon deposition after reaction, free of obvious clusters and high in dispersity, so that the catalyst is not easy to inactivate and has a good prospect in industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic material preparation, and in particular to a method for preparing a hydrophobic propane oxidative dehydrogenation catalyst and application thereof. Background Art

[0002] As a vital bulk chemical raw material, propylene has a rich downstream industrial chain, and its application areas cover plastics, medical devices, home appliances, cosmetics and many other fields. As one of the key areas of petrochemicals, the propylene industry occupies a very important position in the national economy and is also an important indicator of a country's economic development level. Therefore, the development of the propylene industry is not only an important part of supporting the "dual carbon" strategy, but will also promote the high-quality and rapid development of the petrochemical industry.

[0003] The propane dehydrogenation process (PDH) is an important process route for effectively supplementing the supply of propylene due to its advantages such as short process, low investment and high propylene yield. However, the propane dehydrogenation reaction under high temperature conditions can easily lead to further cracking of propylene to form by-products and cause the problem of catalyst carbon deposition and deactivation, which has become the main obstacle to the development of PDH technology. As a technology with low reaction temperature and energy consumption, the propane oxidative dehydrogenation (OPDH) process shows great potential for industrial application. This process uses oxygen or other oxidizing gases (such as CO2 or N2O) to carry out dehydrogenation reactions to produce propylene and water. Compared with traditional dehydrogenation processes, the catalyst in the oxidative dehydrogenation process is not prone to carbon deposition, which significantly reduces the frequency of catalyst replacement and shutdown maintenance costs.

[0004] During the propane oxidative dehydrogenation reaction, due to the presence of oxygen, the hydrogen atoms produced by propane dehydrogenation react with oxygen to generate water. However, in the catalytic reaction of traditional catalysts, the catalyst surface often interacts with the generated water molecules to form hydrogen bonds or adsorb water molecules, which leads to a decrease in catalyst activity. In addition, water vapor can compete with the active sites on the catalyst surface for adsorption, thereby reducing the effective adsorption amount of reactant molecules, resulting in a further decrease in the catalytic activity of the catalyst. Especially in some metal catalyst systems, the adsorption of water vapor may induce phase separation of the metal, which in turn seriously affects the catalytic performance of the catalyst. Summary of the invention

[0005] The present invention aims to provide a preparation method and application of a hydrophobic propane oxidative dehydrogenation catalyst, so as to inhibit the water molecules generated during the catalyst reaction from reacting or adsorbing with the catalyst surface, thereby improving the activity and stability of the catalyst. By the method of the present invention, a hydrophobic functional group is introduced on the catalyst surface to prepare a hydrophobic catalyst, and the contact angle of the prepared hydrophobic catalyst is significantly increased, and excellent water resistance is shown in the water resistance test process of the propane oxidative dehydrogenation reaction, while the metal phase separation phenomenon is inhibited, thereby improving the stability and service life of the catalyst.

[0006] To achieve the above objectives, the present invention adopts the following technical scheme: a preparation method and application of a hydrophobic propane oxidative dehydrogenation catalyst, wherein the catalyst carrier is SiO2, and the catalyst active components are Pt and Sn.

[0007] The active components of the catalyst are loaded on pretreated SiO2, and then different organic hydrophobic segments are grafted to obtain a catalyst with excellent hydrophobic properties.

[0008] Based on the above technical solution, the SiO2 pretreatment temperature is 300-800°C and the pretreatment time is 1-8h.

[0009] Based on the above technical solution, the Pt loading of the catalyst is 0.2-1wt%.

[0010] Based on the above technical solution, the mass ratio of Pt to M is 1:1-1:5, and M includes but is not limited to elements such as Sn, Co, Ni, and Bi.

[0011] On the basis of the above technical solution, the precursor loaded with active components is calcined in a muffle furnace at a temperature of 400-650°C and a calcination time of 2-4h.

[0012] On the basis of the above technical solution, the hydrophobic catalyst is prepared, and the solvent used can be a single solvent or a mixed solution of super dry n-hexane, toluene, dichloromethane or anhydrous ethanol.

[0013] On the basis of the above technical scheme, a hydrophobic catalyst is prepared, and the added hydrophobic coupling agent is not limited to methylsilane coupling agent, chlorosilane coupling agent, aminosilane coupling agent, perfluoroalkylsilane coupling agent, trimethylchlorosilane, methyltrimethoxysilane, etc., and can be a single solvent or a mixed solution.

[0014] On the basis of the above technical solution, the grafted sample is centrifugally washed with the aforementioned solvent and vacuum dried, the centrifugal speed is 3000-10000r / min, the vacuum drying temperature is 60-180°C, and the drying time is 6-36h.

[0015] On the basis of the above technical scheme, the hydrophobic catalyst prepared by the present invention is used for propane oxidative dehydrogenation reaction, the reaction temperature is 400-600°C, and the reaction pressure is 0-0.1Mpa.

[0016] The present invention provides a hydrophobic propane oxidative dehydrogenation catalyst, which exhibits excellent activity and water resistance in the propane oxidative dehydrogenation reaction. By grafting different organic hydrophobic segments, the obtained catalyst H-PtSn@SiO2 exhibits excellent water resistance and structural stability, and can maintain good catalytic performance under long-term reaction conditions.

[0017] Compared with the catalyst used in the existing propane oxidative dehydrogenation, the method provided by the present invention mainly embodies the following advantages: (1) The hydrophobic catalyst of the present invention effectively inhibits the reaction or adsorption of water molecules on the catalyst surface during the propane oxidative dehydrogenation process by introducing hydrophobic functional groups, thereby significantly improving the activity and stability of the catalyst.

[0018] (2) The catalyst of the present invention can effectively prevent the agglomeration of metal clusters, improve the dispersibility of active components, and thus improve the catalyst performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the contact angle diagram of the catalyst Pt1Sn2 / SiO2 in Example 1 that has not been hydrophobically treated.

[0020] Figure 2 This is the contact angle diagram of the catalyst H-Pt1Sn1 / SiO2 obtained by treating with trimethylchlorosilane in Example 2.

[0021] Figure 3 This is the contact angle diagram of the catalyst H-Pt1Sn3 / SiO2 obtained by treating with chloropropylsilane in Example 3.

[0022] Figure 4 This is the contact angle diagram of the catalyst H-Pt1Sn2 / SiO2 obtained by treating with aminomethyltrimethoxysilane in Example 4.

[0023] Figure 5 This is the contact angle diagram of the catalyst H-Pt1Sn1 / SiO2 obtained by treating with perfluorooctyltrichlorosilane in Example 5.

[0024] Figure 6 This is a diagram of the water resistance performance of the catalyst Pt1Sn2 / SiO2 in Example 1 that has not been hydrophobically treated.

[0025] Figure 7 This is a graph showing the water resistance of the catalyst H-Pt1Sn2 / SiO2 obtained by treatment with aminomethyltrimethoxysilane in Example 4.

[0026] Figure 8 This is an electron microscope image of the catalyst Pt1Sn2 / SiO2 catalyst in Example 1 that has not been hydrophobically treated.

[0027] Fig. 9 This is an electron microscope image of the H-Pt1Sn2 / SiO2 catalyst after the water resistance reaction of the catalyst obtained by treating it with aminomethyltrimethoxysilane in Example 4. DETAILED DESCRIPTION

[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose of the invention, the present invention is described in detail below in conjunction with preferred embodiments: Example 1

[0029] Weigh 5gSiO2 and pretreat it at 550°C in a muffle furnace for 3h. Put 0.5gSiO2 carrier after pretreatment in a beaker, add 20mL of anhydrous ethanol, and after ultrasonic treatment for 20min, stir it on a stirrer at 400r / min. Mix the ethanol solution of chloroplatinic acid and stannous chloride in a molar ratio of 1:2, and slowly add it dropwise to the SiO2 solution. The Pt loading is 0.5%. After stirring the mixed solution for 1 hour, transfer it to a 60°C oven to dry. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h to obtain the catalyst Pt1Sn2 / SiO2. The corresponding contact angle diagram is shown in the figure below. Figure 1 shown. Example 2

[0030] Weigh 5g SiO2 and pretreat it at 550°C in a muffle furnace for 3h. Put 0.5g SiO2 carrier after pretreatment in a beaker, add 20mL anhydrous ethanol, and stir it on a stirrer at 400r / min after ultrasonic treatment for 20min. Mix chloroplatinic acid and stannous chloride ethanol solution in a molar ratio of 1:1, and slowly add it dropwise to the SiO2 solution. The Pt loading is 0.5%. After stirring the mixed solution for 1 hour, transfer it to a 60°C oven for drying. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h to obtain the catalyst Pt1Sn1 / SiO2.

[0031] Weigh 0.5g of the calcined sample Pt1Sn1 / SiO2 into a three-necked flask, add 20mL of ultra-dry n-hexane, replace with nitrogen, then drop 1mL of trimethylsilyl chloride, and continue stirring and reacting for 10h. After the reaction is completed, let it stand for 2h, centrifuge at 6000r / min, and dry the obtained sample at 120°C overnight to obtain a hydrophobic catalyst H-Pt1Sn1 / SiO2. The corresponding contact angle diagram is shown in the figure below. Figure 2 shown. Example 3

[0032] Weigh 5g SiO2 and pretreat it at 500°C in a muffle furnace for 4h. Take 0.5g SiO2 carrier after pretreatment and put it in a beaker, add 20mL anhydrous ethanol, and stir it on a stirrer at 400r / min after ultrasonic treatment for 20min. Mix chloroplatinic acid and stannous chloride ethanol solution in a molar ratio of 1:3, and slowly add it dropwise to the SiO2 solution. The Pt loading is 0.2%. After stirring the mixed solution for 1 hour, transfer it to a 60°C oven for drying. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h to obtain the catalyst Pt1Sn3 / SiO2.

[0033] Weigh 0.5g of the calcined sample Pt1Sn3 / SiO2 into a three-necked flask, add 20mL of toluene, replace with nitrogen, then drop 1mL of chloropropylsilane, and continue stirring and reacting for 8h. After the reaction is completed, let it stand for 2h, centrifuge at 6000r / min, and dry the obtained sample at 100°C overnight to obtain a hydrophobic catalyst H-Pt1Sn3 / SiO2. The corresponding contact angle diagram is shown in the figure below. Figure 3 shown. Example 4

[0034] Weigh 5g SiO2 and pretreat it at 600°C in a muffle furnace for 4h. Take 0.5g SiO2 carrier after pretreatment and put it in a beaker, add 20mL anhydrous ethanol, and stir it on a stirrer at 400r / min after ultrasonic treatment for 20min. Mix chloroplatinic acid and stannous chloride ethanol solution in a molar ratio of 1:2, and slowly add it dropwise to the SiO2 solution. The Pt loading is 0.5%. After stirring the mixed solution for 1 hour, transfer it to a 60°C oven for drying. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h to obtain the catalyst Pt1Sn2 / SiO2.

[0035] Weigh 0.5g of the calcined sample Pt1Sn3 / SiO2 into a three-necked flask, add 20mL of dichloromethane, replace with nitrogen, then drop 1mL of aminomethyltrimethoxysilane, and continue stirring and reacting for 8h. After the reaction is completed, let it stand for 2h, centrifuge at 6000r / min, and dry the obtained sample at 100°C overnight to obtain a hydrophobic catalyst H-Pt1Sn2 / SiO2. The corresponding contact angle diagram is shown in the figure below. Figure 4 shown. Example 5

[0036] Weigh 5g SiO2 and pretreat it at 500°C in a muffle furnace for 4h. Take 0.5g SiO2 carrier after pretreatment and put it in a beaker, add 20mL anhydrous ethanol, and stir it on a stirrer at 400r / min after ultrasonic treatment for 20min. Mix chloroplatinic acid and stannous chloride ethanol solution in a molar ratio of 1:1, and slowly add it dropwise to the SiO2 solution. The Pt loading is 0.6%. After stirring the mixed solution for 1 hour, transfer it to a 60°C oven for drying. The dried sample is placed in a muffle furnace and calcined at 550°C for 3h to obtain the catalyst Pt1Sn1 / SiO2.

[0037] Weigh 0.5g of the calcined sample Pt1Sn1 / SiO2 into a three-necked flask, add 20mL of dichloromethane, replace with nitrogen, then drop 1mL of perfluorooctyltrichlorosilane, and continue stirring and reacting for 8h. After the reaction is completed, let it stand for 2h, centrifuge at 6000r / min, and dry the obtained sample at 100°C overnight to obtain the hydrophobic catalyst H-Pt1Sn1 / SiO2. The corresponding contact angle diagram is shown in the figure below. Figure 5 shown.

[0038] from Figure 1-5 It can be seen that the contact angle of the Pt1Sn2 / SiO2 catalyst without hydrophobic treatment is 25.1º, which has obvious hydrophilicity. After the catalyst surface was modified with trimethylchlorosilane, the contact angle of H-Pt1Sn1 / SiO2 increased significantly, showing a certain degree of hydrophobicity. When chloropropylsilane, a chlorine-containing hydrophobic coupling agent, was used, the contact angle of H-Pt1Sn3 / SiO2 increased to 165º, and the hydrophobicity was further improved. In addition, we tried to modify the catalyst surface with coupling agents containing amino groups and perfluoro chains. The results showed that the aminosilane coupling agent showed the best hydrophobic performance, with a contact angle of 170º, followed by chlorosilane coupling agents and perfluorosilane coupling agents. The catalyst modified with methylsilane coupling agent had the worst hydrophobic effect, with a contact angle of only 50.3º.

[0039] The water resistance test was carried out on the catalyst Pt1Sn2 / SiO2 which was not treated with hydrophobicity and the H-Pt1Sn2 / SiO2 which was treated with hydrophobicity by aminomethyltrimethoxysilane. Figure 6 and Figure 7 As shown. For the catalyst Pt1Sn2 / SiO2 that has not been treated with hydrophobicity, its conversion rate dropped significantly after the introduction of 0.05mL / min of water vapor; while the conversion rate of the catalyst H-Pt1Sn2 / SiO2 that has been treated with hydrophobicity has no significant change under the same conditions, which indicates that the hydrophobic treatment can effectively inhibit the adsorption of water molecules on the metal surface. In addition, the catalyst after the water resistance test was characterized by TEM, and the results are shown in Figure 8 and Fig. 9As shown. The catalyst without hydrophobic treatment showed obvious agglomeration after the introduction of water vapor, while the catalyst after hydrophobic treatment was able to maintain a stable particle size under the same conditions. This shows that the hydrophobically modified catalyst can effectively inhibit the sintering of active components during the reaction process and significantly improve the water resistance and reaction stability of the catalyst.

[0040] In general, the emergence and application of hydrophobic catalysts provide innovative ideas and effective solutions for catalytic reactions. By regulating the interaction between catalysts and water molecules, hydrophobic catalysts can not only significantly improve catalytic activity and stability, but also effectively reduce energy consumption and costs, and have significant environmental protection advantages. With the continuous deepening of research on hydrophobic catalysts, their application scope will be more extensive in the future, especially in the fields of energy conversion, environmental protection, and catalyst regeneration and recycling, showing great potential.

[0041] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. The contents not described in detail in this specification belong to the prior art known to professionals in the field. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A preparation and application of a hydrophobic propane oxidative dehydrogenation catalyst, characterized in that: After the catalyst components are loaded on the carrier, different organic hydrophobic segments are then grafted to obtain a propane oxidative dehydrogenation catalyst having good catalytic performance and water resistance.

2. The preparation and use of a hydrophobic propane oxidative dehydrogenation catalyst according to claim 1, characterized in that: The catalyst carrier is SiO2.

3. The preparation and use of a hydrophobic propane oxidative dehydrogenation catalyst according to claim 1, characterized in that: The active component of the catalyst is Pt-M, and the Pt loading is 0.2-1wt%.

4. The preparation and use of a hydrophobic propane oxidative dehydrogenation catalyst as claimed in claim 3, characterized in that: The M is Sn, Co, Ni, or Bi.

5. The preparation and use of a hydrophobic propane oxidative dehydrogenation catalyst according to claim 1, characterized in that: The solvent used in the preparation process of the hydrophobic catalyst can be a single solvent or a mixed solution of super dry n-hexane, toluene, dichloromethane or anhydrous ethanol.

6. The preparation and use of a hydrophobic propane oxidative dehydrogenation catalyst according to claim 1, characterized in that: The hydrophobic coupling agent used in the preparation process of the hydrophobic catalyst is a single solvent or a mixed solution of methylsilane coupling agent, chlorosilane coupling agent, aminosilane coupling agent, perfluoroalkylsilane coupling agent, trimethylchlorosilane, and methyltrimethoxysilane.